Peran Model Fisik dan Digital dalam Perancangan Arsitektur - Prawata, Albertus (ComTech: Computer, Mathematics and Engineering Applications, 2011)
An architectural design process is a process to design an architectural form involving a lot of aspects such as scale, spaces, functions, time and material. The ultimate objective is to create a complete design into a visual media to be presented and actualized in a physical form on a certain site or location. Physical and digital models are media that can be used to visualize an architecture design process from the conceptual step to the final design. Both media have important aspects in design process, as well as able to give design solutions. This article explains the use of physical and digital models with their own characteristics in architectural design process; observes any information from a physical model that can be used and transferred to a digital one; and provides some information about when the physical model and digital model should be used best during the architectural design process.